Do Children and Adults Take Social Relationship Into Account When Evaluating People's Actions?. Issue 5 (12th August 2020) - Marshall, Julia; Wynn, Karen; Bloom, Paul
Abstract : Two studies examined whether children (5‐ and 6‐year‐olds; 8‐ and 9‐year‐olds, n = 214) and adults ( n = 72) consider social relationship when evaluating unhelpful or helpful actions. Participants learned about a person‐in‐need who was (or was not) helped by someone they knew (a friend) and someone they did not know (a stranger). Older children and adults judged an unhelpful friend as meaner than an unhelpful stranger, and judged a helpful stranger as nicer than a helpful friend. Younger children did not judge an unhelpful friend as any meaner than an unhelpful stranger, and they judged a helpful friend as nicer than a helpful stranger. These findings suggest that a mature appreciation of how social relationship matters for evaluation emerges relatively late in development.